Conduction Disturbances and Permanent Pacemaker Implantation After Transcatheter Aortic Valve Replacement: Predictors and Prevention. Issue 4 (14th June 2021) - Tsoi, Melissa; Tandon, Kanul; Zimetbaum, Peter J.; Frishman, William H.
Abstract : Conduction disturbances and permanent pacemaker implantation (PPMI) remain a frequent and important consequence of transcatheter aortic valve replacement (TAVR). Understanding risk factors for TAVR-related conduction disturbances could improve patient selection, procedural techniques, and periprocedural efforts for monitoring and treatment of heart block. Several studies have identified patient-related and procedural factors associated with new-onset left bundle branch block, high-degree atrioventricular block, and the need for PPMI after TAVR. Notable patient-related predictors include preexisting right bundle branch block, membranous septal length, and calcification of the left ventricular outflow tract. Modifiable procedural predictors include device implantation depth, prosthesis oversizing, and valve type. This review aims to summarize the current literature examining predictors of conduction disturbances and PPMI after TAVR, particularly with regard to the newer-generation valve types. We also propose a management algorithm for the management of conduction disturbances postprocedure.